2001
DOI: 10.1046/j.1365-8711.2001.04888.x
|View full text |Cite
|
Sign up to set email alerts
|

Reclassification of gamma-ray bursts

Abstract: We have applied two different automatic classifier algorithms to the BATSE Current GRB Catalog data and we obtain three different classes of GRBs. Our results confirm the existence of a third, intermediate class of GRBs, with mean duration \sim 25-50 s, as deduced from a cluster analysis and from a neural network algorithm. Our analyses imply longer durations than those found by Mukherjee et al. (1998) and Horvath (1998), whose intermediate class had durations \sim 2-10 s. From the neural network analysis no d… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
77
0

Year Published

2002
2002
2019
2019

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 65 publications
(79 citation statements)
references
References 38 publications
2
77
0
Order By: Relevance
“…However, unless the space-time geometry has a very particular structure, the distribution of log f (z) cannot be Gaussian. This means that the Gaussian nature of the distribution of log T 90 must be dominated by the distribution 1 There is also an evidence for the existence of a third intermediate subgroup as part of the long duration group (Horváth 1998;Mukherjee et al 1998;Hakkila et al 2000a,c;Balastegui et al 2001;Horváth 2002), which shows a distinct sky angular distribution (Mészáros et al 2000a,b;Litvin et al 2001). We do not deal with this third group here.…”
Section: Analysis Of the Duration Distributionmentioning
confidence: 99%
“…However, unless the space-time geometry has a very particular structure, the distribution of log f (z) cannot be Gaussian. This means that the Gaussian nature of the distribution of log T 90 must be dominated by the distribution 1 There is also an evidence for the existence of a third intermediate subgroup as part of the long duration group (Horváth 1998;Mukherjee et al 1998;Hakkila et al 2000a,c;Balastegui et al 2001;Horváth 2002), which shows a distinct sky angular distribution (Mészáros et al 2000a,b;Litvin et al 2001). We do not deal with this third group here.…”
Section: Analysis Of the Duration Distributionmentioning
confidence: 99%
“…Early hints to the existence of distinct populations of gamma-ray transients (e.g., Mazets et al 1981;Norris et al 1984), and at least two classes of short-hard (Type-I) & long-soft (Type-II) GRBs (Dezalay et al 1992) have now been extensively corroborated and confirmed by the prompt-emission data E-mail: amir@physics.utexas.edu (AS); nemiroff@mtu.edu (RJN) from independent gamma-ray detector missions (e.g., Kouveliotou et al 1993a;Gehrels, Ramirez-Ruiz & Fox 2009; or follow-up observations of the afterglows or host galaxies (e.g., Zhang et al 2009;Berger 2011Berger , 2014. Although the possibility of more than two classes of GRBs with distinct progenitors has been extensively discussed and considered (e.g., Horvath 1998;Mukherjee et al 1998;Hakkila et al 2001;Balastegui, Ruiz-Lapuente & Canal 2001;Hakkila et al 2004b;Horvath et al 2006;Gehrels et al 2006;Chattopadhyay et al 2007;Horvath et al 2008;Virgili, Liang & Zhang 2009;Gao, Lu & Zhang 2010;Horvath et al 2012;Levan et al 2014;Kbori et al 2014), it has remained a matter of debate and speculation to this date (e.g., Hakkila et al 2000cHakkila et al ,a,b, 2003Hakkila et al , 2004aShahmoradi 2013b;Zhang et al 2014;Levan et al 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Recently Balastegui et al (2001) have applied automatic classifier algorithms and obtain three different classes of GRBs. Further, the intermediate subgroup shows a remarkable angular distribution on the sky (Balázs et al 1998;Balázs et al 1999;Mészáros et al 2000;Litvin et al 2001 the existence of this subgroup is a matter of debate.…”
Section: Introductionmentioning
confidence: 99%